2017
DOI: 10.1080/15412555.2017.1336527
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of NIV for Acute Respiratory Failure in COPD Patients: Results from the International Surveys vs. the “Real World”

Abstract: Non-invasive ventilation (NIV) has been recommended as the  first-line ventilation modality for acute respiratory failure (ARF) due to acute exacerbation of chronic obstructive pulmonary disease (AECOPD) based on strong evidence. However, everyday clinical practice may differ from findings of multiple randomized controlled trials. Physicians and respiratory therapists involved in NIV management have been queried about its utilization and effectiveness. In addition to these estimates, cohort studies and analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Results from a review of international surveys demonstrate that NIV use for AECOPD is increasing worldwide [36]. The authors suggest that this is due to both an increase in the evidence-base in favour of NIV in AECOPD, and an increase in clinician experience of administering NIV.…”
Section: Ward-based Niv As An Alternative To Critical Care Admissionmentioning
confidence: 99%
“…Results from a review of international surveys demonstrate that NIV use for AECOPD is increasing worldwide [36]. The authors suggest that this is due to both an increase in the evidence-base in favour of NIV in AECOPD, and an increase in clinician experience of administering NIV.…”
Section: Ward-based Niv As An Alternative To Critical Care Admissionmentioning
confidence: 99%
“…Here we set out to discuss a landmark paper in this respect: the report of the YONIV trial (Yorkshire Noninvasive Ventilation Trial), published in June 2000, which addressed the key practical questions around the early use of ward-based NIV at the time [ 1 ]. A recent narrative review on the epidemiology of NIV for acute respiratory failure in COPD patients concluded that this dramatic increase in NIV use is probably due to the increased experience of the medical teams, treating sicker patients with comorbidities and utilising NIV outside the intensive care unit (ICU), further confirming the pivotal role of the original trial enabling the early use of acute NIV on medical wards [ 2 ].…”
mentioning
confidence: 99%
“…COPD mainly involves lungs and can also cause extrapulmonary manifestations such as malnutrition, anxiety, depression, and osteoporosis [14, 15, 16]. As a development of environmental pollution and population aging, the incidence rate, disability rate, and mortality rate of COPD are increased [17, 18, 19]. The repetitive acute exacerbation of COPD can cause continuous decrease of lung function mostly complicated with malnutrition, which causes poor immune function and respiratory failure [6,20,21].…”
Section: Discussionmentioning
confidence: 99%